A co-based catalyst, a preparation method and an application method thereof
Patent Information
- Application Number
- CN202410438039.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-04-12
AI Technical Summary
其中,专利CN101531576A用金纳米线作为催化剂,以氧气为氧源催化氧化苯乙烯,转化率过低只有34.1%,反应时间过长且金属于贵金属,价格昂贵;专利CN101979137A在二氧化硅上同时负载钴、铁氧化物,并用氧化钛涂层改性制备了催化苯乙烯环氧化反应的新型催化剂,采用氧气作为该反应的氧化剂,经济环保,但反应的选择性和转化率较低;专利CN101972665A以Co2+为活性组分,采用氨基功能化的介孔分子筛SBA-15吸附Co2+,来制备在氧气或空气条件下催化苯乙烯环氧化反应的催化剂,该催化剂虽然反应活性好、选择性高,且采用经济环保的氧气或空气作为氧源,但制备过程较复杂且催化反应时间长、反应温度高,不利于工业化的量化生产
[0021](1)本发明为无溶剂催化氧化苯乙烯,符合绿色化学的原则,有助于减少废弃物的生成,有助于降低生产成本,为工业上合成氧化苯乙烯和苯甲醛提供了一种可能。
Smart Images

Figure CN118403653B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of industrial catalysis technology, specifically to a Co-based catalyst and its preparation and application methods. Background Technology
[0002] Catalytic oxidation of olefins to oxygen-containing derivatives is a crucial type of oxidation reaction, widely used in industrial production and thus attracting significant research attention. Styrene oxidation, as an important part of olefin oxidation research, has also garnered considerable interest. This is primarily because the products obtained from styrene oxidation, such as styrene oxide and benzaldehyde, are important organic intermediates widely used in the synthesis of pesticides, dyes, coatings, medical chemicals, and fine chemicals. Traditional methods for synthesizing benzaldehyde and styrene oxide include benzyl dichloride hydrolysis and organic peroxide methods. However, these traditional synthetic processes suffer from numerous drawbacks, such as high production costs, complex processes, low yields, severe environmental pollution, and high energy consumption. Therefore, developing green catalysts with high conversion rates and high selectivity for the target products in styrene oxidation is a persistent research focus.
[0003] To address these issues, researchers have developed numerous novel catalysts by loading active components onto porous materials. Among them, patent CN101531576A uses gold nanowires as a catalyst and oxygen as the oxygen source to catalyze the oxidation of styrene, but the conversion rate is too low (only 34.1%), the reaction time is too long, and the metal is a precious metal, making it expensive. Patent CN101979137A simultaneously loads cobalt and iron oxides onto silica and modifies it with a titanium dioxide coating to prepare a novel catalyst for the epoxidation of styrene, using oxygen as the oxidant, which is economical and environmentally friendly, but the selectivity and conversion rate are low. Patent CN101972665A uses Co... 2+ As the active component, amino-functionalized mesoporous molecular sieve SBA-15 is used to adsorb Co. 2+ A catalyst for the epoxidation of styrene under oxygen or air conditions was prepared. Although the catalyst has good reactivity and high selectivity and uses economical and environmentally friendly oxygen or air as an oxygen source, the preparation process is relatively complex and the catalytic reaction time is long and the reaction temperature is high, which is not conducive to industrial-scale production. Summary of the Invention
[0004] The purpose of this invention is to overcome at least one of the defects of the prior art by providing a Co-based catalyst and its preparation and application methods. The Co-based catalyst uses graphene carbon nitride as a support and supports metallic cobalt. The preparation method is a solvent-free catalytic oxidation of styrene, which conforms to the principles of green chemistry, helps to reduce waste generation, helps to reduce production costs, and provides an option for the industrial synthesis of styrene oxide and benzaldehyde.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] One objective of this invention is a method for preparing a Co-based catalyst, comprising the following steps:
[0007] Melamine powder was calcined to obtain a pale yellow graphene carbon nitride powder.
[0008] Graphene carbon nitride and cobalt source were dissolved in ethanol and mixed evenly. The mixture was heated and refluxed in the ethanol solution. After cooling to room temperature, the solid was obtained by filtration. The solid was washed, dried and then calcined to obtain a Co-based catalyst.
[0009] Furthermore, the calcination step includes: heating melamine to 350-750°C at a heating rate of 3-5 min / °C and holding it for 2-4 hours to remove nitrogen and water molecules from the Co salt through high-temperature calcination.
[0010] Furthermore, the washing step includes washing the solid with ethanol and water multiple times in sequence.
[0011] Furthermore, the drying step includes: vacuum drying the washed solid at 75-85°C, preferably 80°C. A vacuum drying temperature below 80°C is not conducive to removing deionized water from the carrier, while a temperature above 80°C will damage the carrier structure.
[0012] Furthermore, the cobalt source is one or more of cobalt nitrate, cobalt acetate, cobalt chloride, or cobalt nitrate hydrate.
[0013] Preferably, the cobalt source is cobalt nitrate hexahydrate.
[0014] Furthermore, the mass ratio of the graphene carbon nitride to the cobalt source is (5-20):100. A moderate loading ensures that the active material exerts the best effect without causing excessive loading and waste. If the mass ratio is higher than the set value, the loading of the active material will be low. If the mass ratio is higher than the set value, the efficiency of the catalyst will be reduced, and material waste will also occur.
[0015] Furthermore, the reflux reaction temperature is 80-90℃ and the reflux time is 3-5h, under which the active substance can be fully attached to the interior and surface of the carrier.
[0016] The second objective of this invention is to provide a Co-based catalyst prepared by the method described above.
[0017] A third objective of this invention is a method for applying the Co-based catalyst described above in the catalytic oxidation of styrene, the method comprising:
[0018] Styrene, tert-butyl hydrogen peroxide and Co-based catalyst are mixed evenly and the reaction is carried out while stirring.
[0019] The molar ratio of styrene to tert-butyl hydroperoxide is 1:(3-4); the mass of the Co-based catalyst is 3wt%-12wt% of the mass of styrene; the reaction temperature is 65-90℃; and the reaction time is 3-12h.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) This invention is a solvent-free catalytic oxidation of styrene, which conforms to the principles of green chemistry, helps to reduce the generation of waste, helps to reduce production costs, and provides a possibility for the industrial synthesis of styrene oxide and benzaldehyde.
[0022] (2) The catalyst prepared by the present invention is applied to the catalytic oxidation of styrene and has good catalytic activity, high selectivity and short reaction time.
[0023] (3) Cobalt is one of the most abundant metals on Earth, and therefore has better sustainability and economy compared with other precious metal catalysts. In addition, carbon nitride (C3N4) is a relatively environmentally friendly material, and the composite catalyst formed by combining it with cobalt (Co) is environmentally friendly and in line with the concept of green catalysis. Attached Figure Description
[0024] Figure 1 This is a comparison graph showing the performance of the 15wt% Co-C3N4 catalyst during the catalytic oxidation of styrene in Examples 1 and 9-11 at different reaction times;
[0025] Figure 2 This is a comparison chart showing the performance of 15wt% Co-C3N4 prepared under different temperature conditions in the catalytic oxidation of styrene in Examples 1, 12-15.
[0026] Figure 3 This is a comparison chart showing the performance of 15wt% Co-C3N4 in the catalytic oxidation of styrene with different styrene / TBHP molar ratios in Examples 1 and 16-18.
[0027] Figure 4 This is a comparison chart of the performance of different 15wt% Co-C3N4 catalyst dosages in Examples 1 and 19-21;
[0028] Figure 5 This is a transmission electron microscope (TEM) image of 15 wt% Co-C3N4 in Example 1 of the present invention;
[0029] Figure 6 This is the X-ray diffraction (XRD) pattern of Co-C3N4 according to the present invention. Detailed Implementation
[0030] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0031] In the following embodiments, unless otherwise specified, the raw materials or processing techniques used are conventional commercially available raw materials or conventional processing techniques in the art.
[0032] In the following embodiments, the prepared products were characterized structurally using the following methods: X-ray diffraction (XRD) scanning was performed on a Rigaku SmartLabSE X-ray diffractometer (Japan) to analyze the structure of the samples; transmission electron microscopy (TEM) images were obtained using a ZEISS GeminiTEM 300 (Germany). Styrene and its products were quantitatively analyzed using a Thermo Fisher TRACE 1300 gas chromatograph (column: TG-WAXMS, 30m × 0.25mm × 0.25μm).
[0033] Example 1
[0034] (1) Preparation of graphene carbon nitride C3N4: Melamine (0.1mol, 12.6g) was ground into fine powder and added to a ceramic crucible. The crucible was heated to 550℃ at a heating rate of 3℃ / min and kept at 550℃ for 4h. The collected light yellow powder (220mg) was graphene carbon nitride (C3N4).
[0035] (2) Synthesis of 15wt% Co-C3N4 catalyst by impregnation method: 2g of the prepared C3N4 and 1.4815g of Co(NO3)2·6H2O were weighed and dissolved in anhydrous ethanol. The solutions were then mixed and heated in an oil bath at 80°C and refluxed for 5 hours. After reflux, the mixture was cooled to room temperature and filtered through a Buchner funnel to obtain a pink solid powder. This powder was washed 3-5 times with ethanol and dried under vacuum at 80°C for 8 hours. The resulting solid powder was calcined in a muffle furnace at 500°C for 2 hours to obtain the 15wt% Co-C3N4 catalyst.
[0036] (3) The catalyst evaluation procedure included: adding 15 mmol of styrene, 45 mmol of TBHP, and 0.1000 g of 15 wt% Co-C3N4 catalyst (catalyst / styrene mass ratio of 6 wt%) to a three-necked flask equipped with a condenser and thermometer. The reaction temperature was 80 °C, the stirring speed was 250 rpm, and the reaction was carried out for 6 h. The results were as follows: Figure 1 As shown, the styrene conversion rate was 81%, the selectivity for benzaldehyde was 36%, and the selectivity for styrene oxide was 60%.
[0037] Example 2:
[0038] Compared with Example 1, most of the contents are the same, except that the calcination temperature of the prepared Co-C3N4 catalyst is different, which is 350°C.
[0039] Example 3:
[0040] Compared with Example 1, most of the contents are the same, except that the calcination temperature of the prepared Co-C3N4 catalyst is different, which is 450°C.
[0041] Example 4:
[0042] Compared with Example 1, most of the contents are the same, except that the calcination temperature of the prepared Co-C3N4 catalyst is different, which is 650℃.
[0043] Example 5:
[0044] Compared with Example 1, most of the contents are the same, except that the calcination temperature of the prepared Co-C3N4 catalyst is different, which is 750℃.
[0045] Example 6:
[0046] The process is largely the same as in Example 1, except that the Co-C3N4 catalyst prepared has a different Co loading, which is 5 wt%.
[0047] Example 7:
[0048] The process is largely the same as in Example 1, except that the Co-C3N4 catalyst prepared has a different Co loading, which is 10 wt%.
[0049] Example 8:
[0050] The process is largely the same as in Example 1, except that the Co-C3N4 catalyst prepared has a different Co loading, which is 20 wt%.
[0051] Example 9:
[0052] The process was largely the same as in Example 1, except for the reaction time, which was 3 hours. The results are as follows: Figure 1 As shown, the styrene conversion rate was 52%, the selectivity for benzaldehyde was 27%, and the selectivity for styrene oxide was 41%.
[0053] Example 10:
[0054] The process was largely the same as in Example 1, except for the reaction time, which was 9 hours. The results are as follows: Figure 1 As shown, the styrene conversion rate was 92%, the selectivity for benzaldehyde was 40%, and the selectivity for styrene oxide was 45%.
[0055] Example 11:
[0056] The process was largely the same as in Example 1, except for the reaction time, which was 12 hours. The results are as follows: Figure 1 As shown, the styrene conversion rate was 99%, the selectivity for benzaldehyde was 43%, and the selectivity for styrene oxide was 30%.
[0057] Example 12:
[0058] The process was largely the same as in Example 1, except for the reaction temperature, which was 75°C. The results are as follows: Figure 2 As shown, the styrene conversion rate was 88%, the selectivity for benzaldehyde was 38%, and the selectivity for styrene oxide was 51%.
[0059] Example 13:
[0060] The process was largely the same as in Example 1, except for the reaction temperature and the reaction time, which was 90°C. The results are as follows: Figure 2 As shown, the styrene conversion rate was 95%, the selectivity for benzaldehyde was 41%, and the selectivity for styrene oxide was 43%.
[0061] Example 14:
[0062] The process was largely the same as in Example 1, except for the reaction temperature and the reaction time, which was 70°C. The results are as follows: Figure 2 As shown, the styrene conversion rate was 73%, the selectivity for benzaldehyde was 30%, and the selectivity for styrene oxide was 62%.
[0063] Example 15:
[0064] The process was largely the same as in Example 1, except for the reaction temperature and the reaction time, which was 65°C. The results are as follows: Figure 2 As shown, the styrene conversion rate was 66%, the benzaldehyde selectivity was 24%, and the styrene oxide selectivity was 66%.
[0065] Example 16:
[0066] The results were largely the same as in Example 1, except that the styrene molar ratio / TBHP molar ratio was different, being 1:2.5. Figure 3 As shown, the styrene conversion rate was 74%, the selectivity for benzaldehyde was 30%, and the selectivity for styrene oxide was 55%.
[0067] Example 17:
[0068] The results were largely the same as in Example 1, except that the styrene molar ratio / TBHP molar ratio was different, being 1:2. Figure 3 As shown, the styrene conversion rate was 68%, the benzaldehyde selectivity was 26%, and the styrene oxide selectivity was 42%.
[0069] Example 18:
[0070] The results were largely the same as in Example 1, except that the styrene molar ratio / TBHP molar ratio was different, being 1:1. Figure 3 As shown, the styrene conversion rate was 42%, the benzaldehyde selectivity was 21%, and the styrene oxide selectivity was 35%.
[0071] Example 19:
[0072] The results were largely the same as in Example 1, except that the mass ratio of the catalyst to styrene used was different, at 3 wt%. Figure 4 As shown, the styrene conversion rate was 68%, the selectivity for benzaldehyde was 29%, and the selectivity for styrene oxide was 48%.
[0073] Example 20:
[0074] The results were largely the same as in Example 1, except that the mass ratio of catalyst to styrene used was different, at 9 wt%. Figure 4 As shown, the styrene conversion rate was 93%, the selectivity for benzaldehyde was 39%, and the selectivity for styrene oxide was 50%.
[0075] Example 21:
[0076] The results were largely the same as in Example 1, except that the mass ratio of catalyst to styrene used was different, being 12 wt%. Figure 4 As shown, the styrene conversion rate was 99%, the selectivity for benzaldehyde was 35%, and the selectivity for styrene oxide was 46%.
[0077] In addition, the present invention also performed transmission electron microscopy and X-ray diffraction (XRD) spectra on the 15wt% Co-C3N4 catalyst obtained in Example 1, as shown in the appendix. Figure 5 and 6 , Figure 5 The image shows a transmission electron microscope (TEM) image of the 15 wt% Co-C3N4 prepared in Example 1. The image reveals that the Co-C3N4 exhibits a thin-layered structure, with wrinkles resembling a thin veil, indicating a porous structure. The C3N4 support maintains its structural integrity, demonstrating that the Co loading does not disrupt the support's structure.
[0078] The figure shows the XRD pattern of 15wt% Co-C3N4 prepared in Example 1. Figure 6 The peaks at 13.1° and 27.3° can be attributed to the (100) and (002) plane structure of C3N4, respectively. More importantly, these peaks become increasingly sharp and pronounced with increasing Co content, indicating enhanced crystallinity of the Co-C3N4 structure. XRD results further confirm the successful preparation and high stability of the Co-C3N4 heterostructure.
[0079] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on its differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. For the apparatus disclosed in the embodiments, since it corresponds to the method disclosed in the embodiments, the description is relatively simple; relevant parts can be referred to the method section. The above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention's technical solution are still within the protection scope of the present invention.
Claims
1. A method for using a Co-based catalyst in the catalytic oxidation of styrene to synthesize styrene oxide and benzaldehyde, characterized in that, The preparation method of this Co-based catalyst includes the following steps: Melamine powder was calcined to obtain graphene carbon nitride; Graphene carbon nitride and a cobalt source were dissolved in ethanol and mixed thoroughly. The mixture was heated and refluxed in the ethanol solution. After cooling to room temperature, the mixture was filtered to obtain a solid. The solid was washed, dried, and then calcined to obtain a Co-based catalyst, wherein the Co content in the Co-based catalyst was 15 wt% of the graphene carbon nitride. The reflux reaction temperature is 80-90℃, and the reflux time is 3-5 h; This application method is carried out under solvent-free conditions and includes the following steps: Styrene, tert-butyl hydrogen peroxide and Co-based catalyst are mixed evenly and the reaction is carried out while stirring. The molar ratio of styrene to tert-butyl hydroperoxide is 1:(3-4); the mass of the Co-based catalyst is 3wt%-12wt% of the mass of styrene; the reaction temperature is 65-90℃; and the reaction time is 3-12 h.
2. The application method according to claim 1, characterized in that, The calcination step includes heating melamine to 350-750°C at a heating rate of 3°C / min and holding it for 2-4 hours.
3. The application method according to claim 1, characterized in that, The washing step includes washing the solid with ethanol and water multiple times in sequence.
4. The application method according to claim 1, characterized in that, The drying step includes: vacuum drying the washed solid at 75-85°C.
5. The application method according to claim 1, characterized in that, The cobalt source is one or more of cobalt nitrate, cobalt acetate, cobalt chloride, or cobalt nitrate hydrate.
6. The application method according to claim 1, characterized in that, The cobalt source is cobalt nitrate hexahydrate.
Citation Information
Patent Citations
Method for preparing benzaldehyde through styrene catalytic oxidation
CN101531576A
Styrene epoxidizing catalyst as well as preparation method and application thereof
CN101972665A
Catalyst for styrene epoxidation and preparation method thereof
CN101979137A